Subsidy to environmental industry in a North-South model of trans-boundary pollution, trade and migration - Nicola Coniglio; Kenji Kondoh (European Regional Science Association (ERSA), 2012)
Differences in environmental regulation between rich and poor countries have caused a geographical relocation of polluting industry from the former to the latter. In several cases the reduction in domestic emissions is at least partly compensated by an increase in trans-boundary pollution which is detrimental to the productivity of environmental sensitive sectors (such as agriculture) industry in a developed country. Can a government in a rich country try to correct the negative consequences of trans-boundary pollution when mechanisms such as binding international agreements are difficult to implement? In this paper we build a simple North-South model of trade where the manufacturing plants are completely outsourced in a developing country and we analyze the effects of a subsidy program to pollution abatement industry located in the North. We find that, contrarily to common intuition, the subsidy to the pollution abatement equipment industry might reduce welfare in the North when the efficiency of the pollution abatement technology is already relatively high and when the wage gap between the North and South is high. In addition we find that international migration might have a positive impact on improving the environmental stock and welfare in the North and might be a more efficient and less distortive way to address the trans-boundary externality.
Keywords: 330